Psychometric Validation of the Moorong Self-Efficacy Scale in People With Spinal Cord Injury: A Brief Report. (October 2014) - Brooks, Jessica; Smedema, Susan Miller; Tu, Wei-Mo; Eagle, Daniel; Catalano, Denise; Chan, Fong
The main study objective was to further evaluate the factorial validity of the Moorong Self-Efficacy Scale (MSES) with 266 Canadians with spinal cord injuries (SCI). Exploratory factor analysis yielded three reliable factors (Interpersonal, Instrumental, and Participation Self-Efficacy) building on earlier studies that extracted two factors. The MSES appears to be a promising rehabilitation assessment tool for individuals with SCI.